A case of mistaken MELD (model for end stage liver disease) score—How an acute hemolytic transfusion reaction falsely altered a patient's transplant status. Issue 4 (22nd February 2023) - Alvi, Saqib; Erony, Sean; Potochny, Evelyn; George, Melissa
Abstract: Background: An acute hemolytic transfusion reaction (AHTR) caused by intravascular hemolysis features a decrease in hemoglobin/hematocrit, reduced haptoglobin, and increases in creatinine, and bilirubin. Acute intravascular hemolysis carries its own morbidity and mortality, especially in the setting of a patient liver disease related pre‐existing alterations in hemostasis. Additionally, AHTR significantly impacts the laboratory values used in calculating the Model for End Stage Liver Disease (MELD) score and thus liver transplant status. Case Report: Herein, we present a case of a patient with hepatorenal syndrome due to ESLD on the transplant list who developed an AHTR due to an evolving anti‐Jka that initially presented as non‐specific reactivity in solid phase adherence testing. This evolving antibody caused intravascular hemolysis and a significant increase in bilirubin from 4.7 to 17.1 mg/dl, thus, raising the MELD score, increasing the predicted short‐term mortality risk, and affecting the patient's transplant status. Results: Acute hemolysis caused significant elevation of bilirubin raising the MELD score which increased both the predicted mortality to 70 percent and the perceived urgency of transplant. The MELD score improved after resolution of the AHTR and clearing of the offending Jka‐positive RBCs. Conclusion: This case highlights the effect of AHTR on parameters used in the determination of MELD score which significantly increases the perceived short‐term mortality and urgency of liver transplant. Therefore, any nonspecific reactivity in initial workup could be due to developing antibodies, and put the patient at higher risk for an acute hemolytic transfusion reaction.